Spinel oxide for oxygen electrocatalysis - Zhou, Ye (2019)
The development of efficient ORR and OER oxide electrocatalysts has become the major challenge in sustainable clean energy technologies, for example, metal-air batteries, electrolyzers, and fuel cells. Gaining fundamental understandings on oxide towards electrocatalysis is a critical component in guiding the efficient design of highly active electrocatalysts. Special attention has been given to the spinel oxide family in this thesis. This dissertation first addresses the effect of transition metal coordination in spinel oxide on electrocatalysis. By tuning the occupation ratio of Co in the tetrahedral and octahedral site, a positive correlation between the OER activities of CoAl2O4 and the octahedral occupancy of Co has been built, demonstrating the leading role of octahedral geometry in oxygen electrocatalysis. Second, the underlying origin of the composition-dependent ORR of Mn-Co containing spinel oxides is examined. Given a fair comparison of the catalyst intrinsic activity, it is found that the distinctive ORR of ZnCoxMn2-xO4 is strongly correlated to the eg electron of active Mn that resulting from the superexchange interactions (Mn[Oh]-O-Co[Oh]) through the edge-sharing [CoxMn1-xO6] octahedra. Third, ultra-small size ferrite nanoparticles are examined as ORR catalyst to check whether the bulk descriptor is applicable to nanoparticle systems. Instead of bulk chemistry, the surface chemistry is identified as the dominating parameter for ORR of nanoparticle oxides. The high surface/bulk ratio of nanoparticles gives a totally different surface composition and the near-surface Mn density revealed from an electrochemical approach strongly correlates to the distinctive ORR activity given by the various ferrite oxide catalysts. Fourth, following the fundamental studies on composition-dependent ORR, a series of ZnFexCo2-xO4 (x=0~2) oxides were studied as OER catalysts to reveal the underlying origin for the composition dependent OER. It is revealed that the Co-O covalency dominates the distinctive OER of ZnFexCo2-xO4 and an enlarged Co-O covalency by 10 ~ 30 at% Fe substitution gives rise to the activity promotion. Unlike the oxygen-deficient perovskite oxides, the lattice oxygen-mediated OER is not considered as a favorable route for the best-performing ZnFe0.4Co1.6O4 catalyst owing to its cation-deficient nature (give a wide energy gap between the O p-band and Fermi level).